Home Use of an Upper Extremity Exoskeleton in Children with SMA: A Pilot Study - Tracy M. Shank; Tariq Rahman (Scholarworks @ WMU, 2021)
Background: People with spinal muscular atrophy (SMA) often have arm weakness resulting in restricted independence and challenges with activities of daily living. An upper extremity (UE) orthosis, the Wilmington Robotic Exoskeleton (WREX), which augments arm movement by providing gravity assistance, was provided to a small cohort of subjects for 1 year. Resulting changes in the subjects' performance were assessed. Method: Five subjects with SMA were asked to use the WREX system for 1 year. Data were collected at baseline and at 6-month intervals. Evaluation tools used were UE range of motion (ROM), the Box and Block Test, the Canadian Occupational Performance Measure (COPM), and the reachable surface area (RSA) using a Microsoft Kinect Sensor. Results: There were no significant changes in UE ROM without the device over time and no significant changes in dexterity after long-term use of the WREX. There were clinically meaningful changes in active ROM while wearing the device compared to without it and clinically meaningful changes in performance and satisfaction while wearing the device. The RSA software did not yield usable results for this population. Conclusion: Wearing bilateral WREX devices resulted in immediate improvements in ROM and function; however, the subjects experienced several barriers, which prevented consistent long-term use.